2010
DOI: 10.3340/jkns.2010.47.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Infraoptic Course of Both Anterior Cerebral Arteries

Abstract: A 28-year-old woman was referred to our hospital with a sudden, very severe headache. Brain computed tomographic angiography showed a saccular cerebral aneurysm at the bifurcation of the left middle cerebral artery and infraoptic courses of both anterior cerebral arteries. The anterior cerebral arteries were seen to arise from the ipsilateral internal cerebral arteries at the level of the origin of the ophthalmic artery, passed underneath the ipsilateral optic nerve, and turned upward at ventral portion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Bilateral proximal infraoptic A1 segments of the ACAs were found arising inferior to the optic strut [ 7 ]. Few cases of bilateral proximal infraoptic A1 segments of the ACAs were reported until recently [ 4 , 5 , 7 , 13 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilateral proximal infraoptic A1 segments of the ACAs were found arising inferior to the optic strut [ 7 ]. Few cases of bilateral proximal infraoptic A1 segments of the ACAs were reported until recently [ 4 , 5 , 7 , 13 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different authors reported cases of aneurysms associated with infraoptic ACAs [ 20 ]. These were found on the AComA or on the A1 or A2 segments of the ACA [ 4 , 5 , 7 , 8 , 13 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. An aneurysm on an infraoptic A1 segment of an azygos ACA was also reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral infraoptic ACAs are less common than unilateral anomalies. 8) One report describes an associated gyral abnormality. 11) The anomalous ACA usually arises from the intra-dural ICA near the level of the ophthalmic artery, as it did in the presented case, or rarely from the extra-dural ICA.…”
Section: Discussionmentioning
confidence: 99%
“…The most important clinical association of such an anomaly is the high incidence of intracranial aneurysms of the ACA-ACoA complex. 5) 8) 14) Recognition of this anomaly is important in planning surgery for ACA-ACoA complex aneurysms in order to identify proximal arterial control of the aneurysm. Failure to account for this anomaly might result in unnecessary dissection along and possible damage to the optic apparatus or inferior frontal lobe during aneurysm repair.…”
Section: Discussionmentioning
confidence: 99%